OPÉRATION DAGUET, OPERATION BROCKET (1990–1991) (Konferensiyalar | Conferences, 2024)
This paper following the invasion of Kuwait by Iraq in 1990, the president of the French Republic, Francois Mitterrand, announces on August 9 the dispatch of the forces of the French army, in particular the aircraft carrier «Clemenceau» and the ships of the National Navy, in order to ensure the protection of the Persian Gulf. This is operation «Salamander». But when on September 14, 1990, the Iraqi army violates international laws and invests the French embassy in Kuwait City, a new operation is set up: «Operation «Daguet»».